POLIGAMI TANPA IZIN PENGADILAN DITINJAU DARI HUKUM ISLAM DAN UU NO 1 TAHUN 1974 - ALI SIBRA MALISI (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2018)
The word polygamy comes from the Greek, polus which means many and gamein or gamos which means marriage. So polygamy is a lot of marriage. Polygamy is a form of marriage where a man at the same time has more than one woman’s wife. As for the reasons Poligami, basically a man can only have a wife. A husband who is married to more than one may be permitted by the parties concerned and the Religious Court has granted permission (Article 3 paragraph (2) of Act Number 1 of 1974). The basis for the granting of polygamy permits by the Religious Courts is set forth in Article 4 paragraph (2) of the Marriage Act (UUP) and also in Chapter IX KHI Article 57. The provisions of polygamy, stipulated in Article 5 of Law Number 1 of 1974 provide conditions against a husband who will be married more than one. Polygamy Procedures. The polygamous procedure under Article 40 of Government Regulation No. 9 of 1974 states that if a husband intends to marry more than one, he is obliged to apply in writing to the court. This is further regulated in Articles 56, 57, and 58 of the Compilations of Islamic Law